In Vitro Comparative Study of the Efficacy of Different Brands Of Amoxycillin - Nasim, Riaz; Hamid, Abdul; Uppal, Taj B. (Journal of Postgraduate Medical Institute, 2011)
Summary This study was designed to establish the efficacy of various brands of Amoxycillin, purchased from the local markets of Peshawar. A total of fifteen brands of Amoxycillin, and the raw material (Amoxycillin) were included in the study. Standard Amoxycilin obtained from oxoid company, London, was used as a control. discs of Amoxycillin were prepared according to standard procedure and were tested on microorganisms isolated from different specimens in the Microbiology Laboratory of Khyber Medical College Peshawar. The brands producing a zone of inhibition of > 18mm were considered effective. The evaluation of data shows that none of the brands of Amoxycillin matched the inhibitory effect of the standard. Some of the products consistently did not produce any inhibitory effect on any of the organisms tested, while others did produce inhibition zone one some of the isolates, but not on others. Even the pure powder of Amoxycillin (the raw material), which was being used by the manufacturers for producing the finished drugs, could not match with standard discs. nodifference of efficacy was found in thepeoducts of the multinational or the local companies.